Assessing the European Parliament’s Democratic Credentials - Stephen Vitkovitch (Romanian Journal of European Affairs)
Doubts persist about the democratic legitimacy and role of the European Parliament in EU decision-making – this article takes a critical look at the body’s democratic credentials. An analysis of voter turnout and the impact the ‘Spitzenkandidaten process’ had on the second-order nature of European elections suggests that the European Parliament suffers from lower turnout than national counterparts, and that the 2014 European elections remained a second-order affair, in spite of the Parliament’s efforts. Existing data and analysis show that while the European Parliament to does a reasonable job translating citizens’ views in relation to left/right issues, the Parliament is more supportive of EU integration than citizens – new data gathered suggest the lack of congruence is pronounced. The European Parliament’s institutional framework set by the Treaties affects its choices, its more limited role in certain areas may lead it to adopt policy positions that are at odds with citizens’ views and security. Ultimately, the European Parliament does not enhance the democratic nature of the EU. The adoption of a more intergovernmental approach to EU decision-making at the expense of the European Parliament would help improve the democratic credentials of EU decision making, and as a minimum further expansion of the Parliament’s powers should be avoided.